Reconstruction of sternal cleft with autologous cartilage graft in an adult - (:unkn) unknown (SAGE Publications Inc., 2015)
Sternal cleft is a rare chest wall deformity associated with various malformations. Primary closure is the gold standard in the newborn period. Alternative techniques are possible for older patients. A 23-year-old woman with a partial sternal cleft and no additional deformity, underwent reconstruction using costal cartilage grafts. Postoperative physical and functional were excellent. © The Author(s) 2014 Reprints and permissions: sagepub.co.uk/journalsPermissions.nav.
Keywords: Adult; congenital abnormalities; sternum; surgical flaps; thoracic surgical procedures